Conceptions of undergraduate students regarding research training in Social Work in Chile - Jarpa-Arriagada, Carmen Gloria; Cárcamo-Vásquez, Héctor Gonzalo; Gallegos-Fuentes, Marcelo Andrés (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
The work sought to reveal the configuration of the conceptions of the students around the stage of design of the research leading to the degree in social work. The study was conducted at a public university in southern Chile. Qualitative method was used, applying an open-ended questionnaire to 14 students. The results indicate that students’ conceptions can be grouped into three categories: cognitive learning, procedural learning and attitudinal learning. In the cognitive the main weakness is the mastery of ontological and epistemic contents; in the procedural aspect there is tension in the application of contents by emotional aspects that affect the student’s decisions; in the attitudinal the student exhibits heteronomous behaviors and requires the permanent presence of the teacher as a guide. In conclusion, the student remains anchored in classical research logics, with little epistemic, theoretical and technical domain. In the binomial theory-practice there is a tendency to emphasize in practice.